Acute effects of the glucagon-like peptide-1 receptor agonist, exenatide, on blood pressure and heart rate responses to intraduodenal glucose infusion in type 2 diabetes. (January 2017) - Thazhath, Sony S; Marathe, Chinmay S; Wu, Tongzhi; Chang, Jessica; Khoo, Joan; Kuo, Paul; Checklin, Helen L; Bound, Michelle J; Rigda, Rachael S; Horowitz, Michael; Jones, Karen L; Rayner, Christopher K
Aim: To evaluate the effects of the glucagon-like peptide-1 receptor agonist, exenatide, on blood pressure and heart rate during an intraduodenal glucose infusion in type 2 diabetes. Methods: Nine subjects with type 2 diabetes were randomised to receive intravenous exenatide or saline control in a crossover design. Glucose (3 kcal min −1 ) was infused via an intraduodenal manometry catheter for 60 min. Blood pressure, heart rate, and the frequency and amplitude of duodenal pressure waves were measured at regular intervals. Gastrointestinal symptoms were monitored using 100 mm visual analogue scales. Results: During intraduodenal glucose infusion (0–60 min), diastolic ( p (0–60)  = 0.03) and mean arterial ( p (0–60)  = 0.03) blood pressures and heart rate ( p (0–60)  = 0.06; p (0–120)  = 0.03)) were higher with exenatide compared to placebo. The increase in the area under the curve for diastolic blood pressure and mean arterial blood pressure was related directly to the suppression of the duodenal motility index with exenatide compared to control ( p  = 0.007 and 0.04, respectively). Conclusion: In type 2 diabetes, intravenous exenatide increases mean arterial blood pressure and heart rate during an intraduodenal glucose infusion, supporting the need for further research with exenatide for its potential use in postprandial hypotension.